Management and employee perceptions of a black advancement programme - Van Niekerk, Ignatius (My University, 1992)
This study adopts an exploratory approach focusing on the perceptions of lower and middle management levels and their subordinate. semi-skilled and skilled Black employees. The purpose of the study was to identify critical factors, as perceived by White lower and middle management levels as well as semi-skilled and skilled Black employees, required to run a successful Black Advancement Programme within specllic organisations. The sample consisted of seventeen White lower and middle level managers and sixty-three Black semi-skilled and skilled employees. Each participant completed e self-administered questionnaire which listed 32 statements reflecting specific Black Advancement activities. Respondents had to indicate to what degree they consider the listed activities will influence the future success of the Black Advancement Programme. Critical factors were identified by comparing the management and employee perceptions of each listed activity. The results of the research confirm that management perceive Black Advancement progress in a significantly more positive way than employees do. The perceptions of the two groups indicate a statistically significant difference regarding the following Black Advancement activities: management clarification of values and corporate commitment by top rnanagement, strategic human resources planning, line management ownership and accountability, targets set or affirmative action, staff attitudes, two-way communlcation, formal training, addressing discriminatory practices and monitoring and tollow-up., These findings correspond with reasons given by Hofmeyr (1989) and Human (1991) as to why Black Advancement Programmes fail. In analysing these findings and the literature it appears that effective Black Advancement is highly unlikely if done in isolation. Black Advancement must be part of a larger Human Resource Strategic Plan and the implementation and reinforcing of plans and policies made. However. being part of a larger Human Resource Strategy implies that Black Advancement should not be a programme on its own, but rather be part of a strategic Staff Deve!opment Programme.
Keywords: Executives -- Training of -- South Africa; Executives, Black -- South Africa.; Occupational training -- South Africa.; Blacks -- South Africa -- Economic conditions.